1995
DOI: 10.1007/bf01075935
|View full text |Cite
|
Sign up to set email alerts
|

Increased potency of vanadium using organic ligands

Abstract: The in vivo glucose lowering effect of orally administered inorganic vanadium compounds in diabetes was first reported in our laboratory in 1985. While both vanadate and vanadyl forms of vanadium are orally active, they are still not well absorbed. We have synthesized several organic vanadium compounds and one compound, bis(maltolato)oxovanadium(lV) or BMOV, has been extensively investigated. BMOV proved effective in lowering plasma glucose and lipids in STZ-diabetic rats when administered in drinking water ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…The specificity of vanadium compounds for different PTPs may be amenable to modification by alteration of ligands (92,93). This study now demonstrates that the relative potency of vanadium may be regulated by intracellular redox state such that increased efficacy may be achieved in tissues under oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…The specificity of vanadium compounds for different PTPs may be amenable to modification by alteration of ligands (92,93). This study now demonstrates that the relative potency of vanadium may be regulated by intracellular redox state such that increased efficacy may be achieved in tissues under oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…1A) provides the opportunity to more fully characterize the action of peroxovanadium within the cell. The action of vanadium can also be modified by organic ligands that facilitate cellular targeting and biochemical specificity (20,21); for example, we found that BMOV (Fig. 1B) induced apoptosis in B cell lineages but enhanced the activation of T cell lineages (15).…”
mentioning
confidence: 96%
“…In recent decades, some vanadyl complexes with several types of organic ligands have been proposed by many research groups for clinical use in humans. [28][29][30][31][32][33][34] To evaluate the insulin-mimetic vanadyl complexes, glucose-uptake in cells or tissues has been monitored, which requires radioisotope (RI) reagents. 5,6,27) In 1995, we proposed a new in vitro assay, based on the inhibition of FFA (free fatty acids)-release from isolated rat adipocytes treated with epinephrine (adrenalin), which is simple and convenient compared with the use of RI reagents.…”
mentioning
confidence: 99%